Stock Market Development and Economic Growth in Malaysia: A Revisit from 1982 to 2014 - Lee Kok Fong; Mori Kogid; Jaratin Lily (Penerbit UTHM, 2020)
The study examines the relationship between the development of the stock market and economic growth in Malaysia using annual data from 1982 to 2014. The development of the stock market represented three indicators, namely the turnover ratio, the shares value traded ratio and the market capitalization ratio. Augmented Dickey-Fuller stationarity test was carried out prior to the use of a bound test approach for co-integration and causality testing. The findings of the co-integration analysis showed that there is evidence of a long-run relationship between economic growth and the development of the stock market. Further examination of the causal relationship showed proof of the shortrun interaction between economic growth and the development of the stock market. These findings may be of importance to policymakers in formulating growth policy and financial decision-making by investors.